Mechanistically derived dispersal kernels explain species‐level patterns of recruitment and succession. Issue 11 (18th October 2018) - Sullivan, Lauren L.; Clark, Adam T.; Tilman, David; Shaw, Allison K.
Abstract: Species‐level dispersal information can give mechanistic insights into how spatial processes impact plant communities. Unfortunately, field‐based estimates of the dispersal abilities of multiple members of a community are often lacking for many plant systems. Here, we provide a simple method for measuring dispersal ability for large numbers of grassland plant species based on functional traits. Using this method, we estimated the dispersal ability of 50 co‐occurring grassland species using the Wald Analytical Long‐distance Dispersal (WALD) model. Grassland plants species are often used for developing community theory, yet species‐level estimates of their dispersal abilities are comparatively rare. We use these dispersal measurements to examine the relationship between species dispersal abilities and successional dynamics using data from a 90‐yr old field chronosequence. We find that our estimated dispersal measurements matched field‐based establishment observations well, and estimated species colonization, competitive, and establishment abilities. We hope that this method for measuring dispersal ability of multiple species within a community, and its demonstrated ability to generate predictions for spatial ecology, will encourage more studies of the explicit role of dispersal in plant community ecology.